HYDROTHERMAL PHASE STABILIZATION OF 2-LINE FERRIHYDRITE BY BACTERIA - Kennedy C.B.; Scott S.D.; Ferris F.G. (My University, 2004)
Poorly ordered 2-line ferrihydrite deposits from the caldera of Axial Volcano, a site of hydrothermal vent activity along the Juan de Fuca Ridge, are characterized by an abundance of bacterial structures resembling Gallionella ferruginea, Leptothrix ochracea and PV-1 filaments encrusted with nanoparticulate ferrihydrite. Ferrihydrite formed in the absence of bacteria can be metastable and will subsequently react to form more structurally ordered iron oxide phases such as hematite or goethite. Inspection of samples from 2-day 80 °C aqueous heating experiments by electron microscopy and X-ray diffraction revealed that a natural sample of bacteriogenic ferrihydrite from Axial Volcano did not undergo a phase transition, whereas synthetic ferrihydrite, absent of bacteria, transformed to hematite after 2 days. A series of bacterial-ferrihydrite composites exhibited decreasing amounts of transformation to hematite with increased amounts of Fe(III) bound to bacteria. Complete inhibition was observed when 50% of the total Fe was bound as ferric iron and 50% was present as ferrihydrite. For the synthetic ferrihydrite samples containing bacteria, the inhibition of ferrihydrite transformation is attributed to microbial surface functional groups (i.e. carboxyl, phosphoryl, amine) constraining the Brownian motion of surface bound ferrihydrite nanoparticles, thereby eliminating the aggregation and rotation of particles required for crystal growth. The stabilization of ferrihydrite will prolong the longevity of a highly reactive mineral phase, which may have implications for marine geochemistry and environmental remediation. Preservation of bacteria encrusted with transformation resistant ferrihydrite may enhance the potential usefulness of bacteriogenic ferrihydrite to harbour bacterial microfossils, imparting these types of samples with potential use for paleontology and astrobiology.
Keywords: Bacteria; Ferrihydrite; Phase transition; Inhibition; Hydrothermal; Axial Volcano